﻿Mosaici e pittura romana del Medioevo : pregiudizi e omissioni - Pace, Valentino (RACAR : Revue d'art canadienne / Canadian Art Review, 1985)
A new critical approach to the evaluation of mediaeval Roman mosaics and paintings is outlined. Beginning with a review of the modern consideration of the celebrated absidal mosaic in Santi Cosma e Damiano, issues of iconography, stylistic language and artistic identity are discussed concerning well-known decorative examples from the 6th to the late 13th century in Rome. Emphasis is placed on the 13th century and especially on Torriti’s mosaics in Santa Maria Maggiore and San Giovanni in Laterano, and on Cavallini’s rapport with the Master of Isaac.